Pragmalinguistic analysis of the major players in social networks: memes of COVID-19 and Russia's invasion of Ukraine in Spain - Preciado Jover, Lucía (2022)
Historical events between 2020 and the beginning of 2022, such as the global pandemic of COVID- 19 and the outbreak of a possible Third World War, have been the ideal context for practically the entire world population to have resorted to escape routes at their fingertips, such as social networks. The use of these applications favors interaction and contact among the population and has led to a considerable increase in the creation of minimal structures loaded with humor and irony: memes. The purpose of this study is to perform a pragmalinguistic analysis of memes related to COVID-19 and Russia's invasion of Ukraine in order to define and delimit their characteristics. For this purpose, based on a selection of 30 memes, we are going to analyze the following features: structure, intention, subject matter, characters appearing in the memes' images and linguistic marks of humor and irony. The results show that it is the use of the image in a given context that produces a humorous effect. Similarly, it is the proximity of the topic that generates content and interest for the production of memes.